Pneumococcal Pneumonia Resembling Acute Myocardial Infarction in an Adolescent Male. Issue 1 (January 2020) - Chiong, Yee Keow; Tan, Ian; Lim, Terence CW; Thong, Wen Yi; Chan, Mark Y; Chan, Si Min
Abstract : Myocarditis is commonly associated with viruses. However, we present a novel case of a teenager with pneumococcal pneumonia and bacteremia complicated by myocarditis and rhabdomyolysis, presenting with features of acute ST-elevation myocardial infarction and cardiogenic shock. Physicians should be aware that Streptococcus pneumonia e infection, like Group A Streptococcus, can mimic acute myocardial infarction in young males without cardiovascular risk factors.